Revisiting the Informal Sector A General Equilibrium Approach - Chaudhuri, Sarbajit. (Springer New York : Imprint: Springer, 2010)
The last 50 years have seen unprecedented population growth and urbanization, particularly in developing countries. However, economic development in these countries has failed to generate adequate employment and income opportunities in the modern sector. This imbalance has compelled the surplus labor force to generate its own means of employment and survival in the informal sector. The informal sector is economic activity that is neither taxed nor monitored by a government. Its main characteristics are: easy entry for new enterprises, reliance on indigenous resources, family ownership of enterprises, small scale operations and low productivity, labor-intensive and adapted technology, reliance of workers on informal sources of education and skills, unregulated and competitive markets and lack of governmental support. This timely, comprehensive book provides insight into the diverse aspects of the informal sector, its role in the context of unemployment, child labor, globalization and environment, as well as its multi-faceted interaction with the other sectors of the economy. It outlines previous doctrines that portray the informal sector as a sector of last resort, and elucidates newer approaches that see the informal sector as dynamic and instrumental in ameliorating unemployment and propelling the developing economies towards growth and prosperity. Finally, the book critically reviews the contradictions within both to trace the nature and direction of desirable policy parameters. It is an invaluable reference for academics and students in development and international economics. The book’s findings will also be useful to policymakers for application to development projects.